2015
DOI: 10.1371/journal.pone.0128192
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Renal Function and Oxidative Status Associated with the Hypotensive Effects of Oleanolic Acid and Related Synthetic Derivatives in Experimental Animals

Abstract: PurposeThe triterpene oleanolic acid (OA) is known to possess antihypertensive actions. In the present study we to compared the effects of the triterpene on mean arterial blood pressure (MAP) and kidney function following acute administration in normotensive animals with those of its related oleanane synthetic derivatives (brominated oleanolic acid, Br-OA and oleanolic acid methyl ester, Me-OA). We also used experimental models of hypertension to further explore the effects of sub-chronic oral OA treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
(59 reference statements)
0
36
0
Order By: Relevance
“…And also OA reduced the malondialdehyde (MDA) as compared to the control group. [79] Antiepileptic activity Ethnobotanically, the plant is mentioned to be used for epilepsy in Nepal and Darjeeling region of India. Geetha et al (2010) reported the antiepileptic activity of methanolic extract of V. articulatum aerial part in albino rats and mice.…”
Section: Antiulcer Activitymentioning
confidence: 99%
“…And also OA reduced the malondialdehyde (MDA) as compared to the control group. [79] Antiepileptic activity Ethnobotanically, the plant is mentioned to be used for epilepsy in Nepal and Darjeeling region of India. Geetha et al (2010) reported the antiepileptic activity of methanolic extract of V. articulatum aerial part in albino rats and mice.…”
Section: Antiulcer Activitymentioning
confidence: 99%
“…Systolic (SBP) and diastolic (DBP) blood pressure, body weight, 24-hour water and food consumption and urine output volume were recorded. SBP and DSP were monitored using the non-invasive tail cuff method with photoelectric sensors (IITC Model 31 Computerised Blood Pressure Monitor, Life Sciences, Woodland Hills, California, USA) as previously described [16]. Urine samples were collected for the analysis of nephrin, albumin and creatinine concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Nephrin, SOD and plasma insulin concentration were measured using ELISA kits (Elabscience and Biotechnology, WuHan) per the manufacturer’s instructions. MDA concentration was measured using an established laboratory protocol [16]. Briefly, kidney tissue (50 mg) was homogenized in phosphoric acid (500 µL, 0.2%) after which the homogenate was supplemented with phosphoric acid (400 mL, 2%).…”
Section: Methodsmentioning
confidence: 99%
“…Mean arterial pressure was monitored using the non-invasive tail-cuff technique with photoelectric sensors (IITC Model 31 Computerised Blood Pressure Monitor; Life Sciences, Woodland Hills, CA, USA), as described previously. 24 All measurements were conducted at 1000 h.…”
Section: Experimental Protocolmentioning
confidence: 99%